Representation of Visual Content in English Textbooks Toward the Pancasila Student Profile in "English for Nusantara" - Tiara Wardani; Imam Ghozali (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2026)
This study examines the representation of the Pancasila Student Profile in the visual content of the English textbook English for Nusantara used at the junior high school level. The textbook is an official publication of the Indonesian Ministry of Education, Culture, Research, and Technology and is implemented nationally as part of the Merdeka Curriculum for Grade VIII students. The study focuses on how visual elements such as illustrations, images, and comic strips represent Pancasila values. This research employs a qualitative approach using qualitative content analysis. The data consist of visual materials taken from the English for Nusantara textbook. Data were collected through non-participant observation supported by field notes and analyzed using Critical Discourse Analysis to examine ideological meanings and value representations. Methodological triangulation involving experts in English Language Teaching was applied to ensure credibility. The findings show that although the textbook contains many visual elements, only a limited number explicitly represent the Pancasila Student Profile. Most visuals mainly function as instructional supports for English language learning. Therefore, this study concludes that while English for Nusantara integrates Pancasila values, further improvement is needed to make these values more explicit and effective in supporting students’ character development in the Merdeka Curriculum context.